Analysis of Fishing Operational Cost and Fishermen's Income at TPI Lappa, Sinjai Regency - Yuyun Aulia Putri; Wa Ode Rayyani (Jurnal Studi Multidisiplin Ilmu, 2025)
Purpose: This study aims to analyze the fishing operational cost incurred by fishermen and the income they earn at Tempat Pelelangan Ikan or Fish Auction Center, Lappa in Sinjai Regency. Methodology: A descriptive quantitative approach was applied. Respondents consisted of five active fishermen selected through purposive sampling based on at least five years of continuous fishing activity and regular sale of catch at Fish Landing Center (Tempat Pelelangan Ikan or TPI) Lappa. Data were collected through structured interviews, observation, and documentation, then analyzed using descriptive statistics covering operational cost, total revenue, net income, average values, and percentage share, presented in tabular form.Results: The average operational cost incurred by fishermen reached IDR1,180,000 per trip. Fuel accounted for the largest component, averaging IDR700,000, followed by maintenance, consumption, and ice costs. Average total revenue reached IDR4,440,000 per trip, while average net income reached IDR3,260,000 per trip.Conclusions: Efficient management of operational cost, particularly fuel use, plays a role in supporting higher net income among fishermen, while differences in income across respondents are also shaped by catch volume and selling price.Limitations: The study involved only five fishermen and focused solely on operational cost and income, so the findings cannot be broadly generalized.Contributions: This research offers an empirical picture of the operational cost structure and income of fishermen and may serve as a consideration in improving the efficiency of capture fisheries and the welfare of fishing households.